Answer:
Some of the Exponents = -2 that is true, not 2.
Step-by-step explanation:
Let's check one at a time.
(a)The 6 without an exponent is equivalent to the 6 having a 0 exponent.
[tex]6^{0} =1[/tex] and [tex]6^{1}[/tex] = 6 (no exponent. 6 [tex]\neq[/tex] 1 therefore this statement is False.
(b)The sum of the exponents is -2.
let's check , if the base is same we can add the exponents that is the exponent rule.(well established).
if we add exponents in the given expression we get.
[tex]6^{1} 6^{0} 6^{3} =6^{1+0+(-3)} =6^{-2}[/tex], therefore we can see that the sum of the exponents = -2 this is true.
(c) An equivalent expression is 65.6-7, lets evaluate our above expression, it is equal to [tex]\frac{1}{36}[/tex] which we can see that [tex]\frac{1}{36} \neq 65.6-7[/tex] ,therefore this statement is false as well.